If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 4b + 8c = 0 Solving 2a + 4b + 8c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4b' to each side of the equation. 2a + 4b + -4b + 8c = 0 + -4b Combine like terms: 4b + -4b = 0 2a + 0 + 8c = 0 + -4b 2a + 8c = 0 + -4b Remove the zero: 2a + 8c = -4b Add '-8c' to each side of the equation. 2a + 8c + -8c = -4b + -8c Combine like terms: 8c + -8c = 0 2a + 0 = -4b + -8c 2a = -4b + -8c Divide each side by '2'. a = -2b + -4c Simplifying a = -2b + -4c
| x+2(x-6)=x-11 | | 3(6+8)=48 | | 2a+4b+15= | | 2a+4b-15= | | 2(9x+5)=12x-2 | | x-7+3x=18 | | -95.552=-3.2(3.2n+6.5) | | 3x+75=360 | | -2a+15-4b= | | 2a+15-4b= | | x+31+29=90 | | Y=3.4x-0.2 | | 8(x+5)=2(4x+1)+38 | | 725=15n+5 | | 26=7x+6-(-3x) | | 2x+128=180 | | 8(3x-7)=2(12x+8) | | A*6+4=14 | | 2g^3h^3/14g | | 88/3-8 | | 14+7a=28 | | 32-8/3 | | 9x/x^2 | | x^2+7x+44= | | (x-7)*7=6x-6 | | 2(4x-1)=3(x+2)+5 | | f(-4)=4x-2 | | 65327=.8x | | c=24n+4 | | 6(x-11)=15-14x | | 6x+6x+2+7=4x+5+7x | | 3x-1/x-4 |